Discourse analysis of the personal brand construction of a group of Finnish managers on Twitter - Hämäläinen, Katariina (2017)
In this study, the objective was to understand how Finnish managers build their personal brand on Twitter. More specifically, the goal was to find out what kind of managerial identities can be discerned based on the discourses, linguistic means, and rhetoric through which Finnish managers brand themselves on Twitter. The study was conducted as qualitative research, using discourse analysis as the analysis method. The research data for this study were collected from the publicly available Twitter profiles of 12 Finnish managers who actively use the platform. Previous literature and theories regarding the concepts of personal branding and identity work, as well as Watson’s identity construction model, were used as a theoretical basis. Consequently, five identity images were found that represent the personal brands of Finnish managers. These images were the Patriot, Philanthropist, Fan, “Me Behind the Scenes,” and Winner.